Sinergi Antar Aktor Dalam Pencegahan Covid 19 di Desa Pakkabba - Abdul Rahman (Fakultas Ilmu Sosial dan Ilmu Politik, 2022)
At the end of 2019 the world was shocked by the outbreak of a disease caused by a virus which was later given the name covid 19. Indonesia also could not avoid the attack of the virus. Steps taken to overcome the spread of the virus, namely by reducing and limiting human movement. These policies have an impact on economic life and the provision of education. The Government of the Republic of Indonesia has established social distancing as part of a health protocol that must be implemented throughout Indonesia, including in rural areas. On that basis, this article aims to elaborate on the involvement and synergy between actors in Pakkabba Village in preventing covid 19. To answer this problem, research was carried out by collecting data through observation and interviews. The results showed that the pace of development of covid 19 could be inhibited in Pakkabba Village because of the synergy between actors and the community in enforcing and complying with health protocols set by the government.